TOTAL NON-STRUCTURAL CARBOHYDRATE (TNC) OF THREE CULTIVARS OF NAPIER GRASS (Pennisetum purpureum) AT VEGETATIVE AND REPRODUCTIVE PHASE - Budiman, B.; Soetrisno, R.D.; Budhi, S.P.S.; Indrianto, A. (Diponegoro University, 2011)
An experiment was conducted to determine Total Non-structural carbohydrates (TNC) of threecultivars of napier grass (Pennisetum purpureum) harvested at vegetative and reproductive phases. Thecultivars tested were Taiwan (Gt), King (Gk) and Mott (Gm) and arranged in a 3 x 2 of treatments withfour replicates following nested design. The results showed that the highest sugar content (P<0.01) wasfound in Gt cultivar and the lowest was in Gm cultivar. The highest starch content (P<0.01) was found inGk cultivar and the lowest was in Gt cultivar. TNC content of Gt and Gk cultivars were not significantlydifferent, but both were significantly higher (P<0.01) compared with the Gm cultivar. It can beconcluded, that there were differences in TNC between cultivars, however, the TNC content in Gkcultivar was not different with Gt cultivar, while Gm cultivar have the lowest (P<0.01) TNC content. Atreproductive phase all cultivars have higher (P<0.01) TNC and starch content than at vegetative phase